A Comprehensive Review of Improvement of Image Contrast in Case of Poor Light - Mishra, Pratiksha; Sinhal, Amit; Tomar, Deepak Singh (International Journal of Computer Sciences and Engineering, 2014)
In this paper, we are reviewing several research papers regarding study and analysis towards improvement of image contrast in case of poor light. In this paper we most focus on many algorithms that has been designed for enhancement of image, At the end, a study has been made by comparing all the proposed parameters that with certain advantages and having limitations too, that have been conducted a relevant experimental analysis to evaluate both their robustness and their performance. Our review work involves a comparative study of Improvement of Image Contrast for image enrichment with respect to the following parameter Performance, Scalability, Image enhancement, Image Acquisition, Applying Morphological operators, Detecting and extracting the background, Applying contrast enhancement operators:- block analysis and opening by reconstruction, Applying image enhancement techniques like image sharpening etc.